Experimental Evaluation of a Procedure for SMF Continuity Plate and Weld Design - Mashayekh, Adel; Uang, Chia-Ming (Engineering Journal, 2018)
The AISC Seismic Provisions require that continuity plates in a special moment frame (SMF) welded moment connection be connected to the column flanges by complete-joint-penetration groove welds. Tran et al. (2013) have proposed a design procedure that allows the designer to evaluate the required forces in the continuity plates such that more economical welds (e.g., fillet welds) can be used; the required thickness of the continuity plates also need not be the same as that prescribed in the AISC Seismic Provisions. With some minor modifications to the original design procedure, two one-sided reduced beam section moment connection specimens were designed and constructed for experimental verification of the proposed design procedure. To evaluate the effect of potential column kinking on the fillet-welded joints between the continuity plates and the column flanges, weaker panel zones that still satisfied the code requirement were used. Although the AISC Seismic Provisions implicitly assume that continuity plates should remain essentially elastic, the continuity plate thickness of one specimen was intentionally undersized to evaluate the effect of continuity plate yielding on the connection performance. Test results showed that using fillet welds is feasible; no damage was observed in these fillet welds, and the connection performance was not affected by the type of weld joints used. The design procedure also indicates the significant effect of in-plane moment in the continuity plate’s strength check, especially when shallow columns are used.